2008
DOI: 10.1103/physrevlett.101.248106
|View full text |Cite
|
Sign up to set email alerts
|

Motional Coherence in Fluid Phospholipid Membranes

Abstract: We report a high energy-resolution neutron backscattering study, combined with in-situ diffraction, to investigate slow molecular motions on nanosecond time scales in the fluid phase of phospholipid bilayers of 1,2-dimyristoyl-sn-glycero-3-phoshatidylcholine (DMPC) and DMPC/40% cholesterol (wt/wt). A cooperative structural relaxation process was observed. From the in-plane scattering vector dependence of the relaxation rates in hydrogenated and deuterated samples, combined with results from a 0.1 µs long all a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
5
45
0
Order By: Relevance
“…The faster process can, therefore, be tentatively assigned to lipid motion confined to a certain area in the membrane. This observation is in agreement with recent results, which suggest that lipids move coherently in loosely bound clusters of ≈30Å diameter, rather than as independent molecules [9][10][11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The faster process can, therefore, be tentatively assigned to lipid motion confined to a certain area in the membrane. This observation is in agreement with recent results, which suggest that lipids move coherently in loosely bound clusters of ≈30Å diameter, rather than as independent molecules [9][10][11].…”
Section: Discussionsupporting
confidence: 83%
“…And ballistic lipid motion in fluid membranes has indeed been recently reported from quasielastic neutron scattering (QENS) using a neutron backscattering spectrometer [8]. Furthermore, it has been reported that lipids move coherently in loosely bound clusters, rather than as independent molecules [9][10][11]. A "hopping" diffusion of lipids into nearest neighbour sites was observed in single supported bilayers [12], and, recently, it has also been suggested that there is a flow-like component to the motion of the lipid molecules over long length scales [11].…”
Section: Introductionmentioning
confidence: 98%
“…For membranes, a shift of the main phase transition to higher temperatures with decreasing water content is already known for quite some time. 11 In recent years, neutron scattering studies of membrane dynamics focused on highly hydrated samples, [12][13][14][15] but only a few of these studies took hydration effects explicitly into consideration, e.g., König et al 14 In this work, we investigated the hydration influence on the dynamics of model membranes by quasielastic neutron scattering ͑QENS͒ and elastic incoherent neutron scattering. Model membrane systems such as 1,2-dimyristoyl-snglycero-3-phosphocholine ͑DMPC͒ show a similar thermodynamical behavior as real cell membranes 16 and are therefore often used to mimic their more complex natural counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…In mammal organisms, vesicular membranes often serve as natural carriers. It is assumed that functional properties of a membrane depend likewise on its composition-dependent structure and dynamics [8,9]. In order to gain insight into membrane function, specific material properties, such as, e.g., the bilayer bending rigidity κ can be aimfully influenced.…”
mentioning
confidence: 99%